PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTU MEDIA POWER POINT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI & BUDI PEKERTI KELAS XI IPA DI SMA N 2 SENTAJO RAYA - Fitri Yana; Andrizal Andrizal; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2021)
This study aims to increase student motivation in Islamic education and character in class XI IPAA. the type of research used is Classroom Action Research (PTK). This research was conducted in 3 cycles, each cycle consisting of 4 stages, namely planning, implementing, observing and reflecting. The subjects of this study were 24 students of class XI IPAA. The data collection techniques used were observation, interview and documentation. The results showed that the implementation of the cooperative learning strategy type make a match assisted by power point media can increase student motivation. In the pre-cycle activity, the average result of student learning motivation observation was 42.40%. This is certainly not said that student motivation is high, because the indicator of student learning motivation is said to be high / good if it reaches 75%. After applying the cooperative learning strategy type make a match assisted by power point media, the students' learning motivation has increased. In the third cycle student learning motivation has reached the indicator 75% overall.